PENGEMBANGAN INSTRUMEN TES DENGAN PENDEKATAN OPEN ENDED PADA MATERI OPERASI HITUNG BILANGAN KELAS III SD - Rahmadini, Laylatul Putri; Surayanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The evaluation of mathematics learning in elementary schools still mostly uses tests in the form of questions with definite answers. This does not accommodate the various ways of thinking of students, especially in understanding number calculation material. This study aims to create a test instrument with an open ended approach to third grade elementary school that is valid, practical, and effective. The research subjects involved third grade students from SDN Kesamben 07, SDN Kesamben 06, and SDN Kesamben 04. This study used the ADDIE model, which consists of several stages, namely analysis, design, development, implementation, and evaluation. During the analysis stage, it was found that there was a need for an evaluation instrument that could measure the process and variety of ways students solve problems. The design stage produced a question grid with an Open Ended approach and critical thinking ability indicators. In the development stage, the test instrument obtained a very high validity level, namely 97.90% from subject matter experts and 99% from instrument experts. In the implementation stage, a practicality test involving teachers and students showed a practicality level of 89.29% from teachers and 83% from students in the very practical category. The effectiveness of the instrument was evident from the increase in the average student score from 53.90 on the initial test to 90.04 on the final test, with a significance level of 0.000 and an N-Gain value of 0.7823, which is classified as a high improvement. Thus, the open ended based test instrument is feasible and effective for use as an alternative for evaluating mathematics learning in elementary schools.